Identification and precision therapy for three maturity-onset diabetes of the young (MODY) families caused by mutations in the HNF4A gene - Zhang, Juan; Jiang, Yanyan; Li, Jianhua; Zou, Haiyin; Yin, Li; Yang, Yang; Yang, Lei (Frontiers in Endocrinology, 2023)
Heterozygous pathogenic variants in HNF4A gene cause maturity-onset diabetes of the young type 1 (MODY1). The mutation carriers for MODY1 have been reported to be relatively rare, in contrast to the most frequently reported forms of MODY2 and MODY3. In this study, three heterozygous missense mutations in the HNF4A gene, I159T, W179C, and D260N, were identified in the probands of three unrelated MODY families using whole exome sequencing (WES), one of which (W179C) was novel. Cascade genetic screening revealed that the mutations co-segregated with hyperglycemic phenotypes in their families. The molecular diagnosis of MODY1 has partly transformed its management in clinical practice and improved glycemic control. The proband in family A successfully converted to sulfonylureas and achieved good glycemic control. Proband B responded well to metformin combined with diet therapy because of his higher body mass index (BMI), and therefore we did not consider switching to sulfonylureas from metformin. The proband in family C, with paternalderived mutations, had markedly defective pancreatic β-cell function due to the superposition effect of T2DM susceptibility genes from the maternal grandfather, and he is currently treated with insulin. In silico analysis using PyMOL showed that the I159T and D260N mutations altered polar interactions with the surrounding residues, and W179C resulted in a smaller side chain. Structural alterations in these mutations may lead to defects in protein function, further contributing to the hyperglycemic phenotype of mutation carriers.